LITERATUR REVIEW: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IBU HAMIL MEMILIH MELAKUKAN PERSALINAN DI FASILITAS KESEHATAN DI INDONESIA - Aulia Zahara; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Childbirth is a physiological state experienced by everyone. However, these physiological conditions become pathological when the mother does not know these physiological conditions and helpers or nurses do not understand how physiological delivery should be and how to manage it in such a way as to reduce maternal mortality. The purpose of this study is how the factors that influence pregnant women in giving birth at health facilities and what the opinion of the mother's knowledge about it. By scanning the Google Scholar database for the terms "Knowledge," "Education," and "Selection of delivery site," the literature study research method with a systematic review design based on descriptive analysis, resulted in a literature review journal. The type of data used by the author in this study is secondary data. Several studies yielded positive results for this study, and it is clear that there is a correlation with the knowledge of pregnant women. According to the findings of this study, we received information that there are still many mothers who choose to give birth in a place that is not a puskesmas, namely at home, where deliveries at a puskesmas should be better done in a health facility because they can be handled better and serve patients who are pregnant